Hubungan Antara Perilaku Agresi Verbal Dengan Kontrol Diri Pada Remaja Di Kota Bekasi - Ridho Andi Nugroho; Lenny Utama Afriyenti (CV. ITTC INDONESIA, 2025)
This study aims to determine the relationship between self-control and verbal aggression behavior among adolescents in Bekasi City. Verbal aggression is defined as deliberate actions intended to harm others psychologically through negative words or verbal expressions, while self-control refers to an individual's ability to regulate impulses, emotions, and behavior according to social norms. The research employs a quantitative approach with a correlational design. The subjects were 400 adolescents aged 13–18 years, selected through a simple random sampling technique. The instruments used were a verbal aggression scale based on Infante & Wigley's (1986) theory and a self-control scale based on Averill's (1973) theory. Data were analyzed using Pearson correlation with SPSS software version 27. The findings show a significant negative relationship between self-control and verbal aggression behavior among adolescents (r = -0.741, p < 0.05). This indicates that adolescents with high levels of self-control tend to exhibit lower levels of verbal aggression. Additionally, further analysis reveals differences in verbal aggression levels based on age and residential environment. Adolescents aged 14 years exhibited the highest levels of verbal aggression, while those aged 18 years showed the lowest levels. Regarding residential environment, adolescents living in suburban areas had higher average levels of verbal aggression compared to those living in urban or residential areas. This study concludes that self-control plays a crucial role in reducing verbal aggression among adolescents. The practical implications of the research include the development of educational programs and interventions focused on enhancing self-control to prevent aggressive behavior.